Endoscopic full thickness resection (EFTR) of colorectal neoplasms with the Full Thickness Resection Device (FTRD): Clinical experience from two tertiary referral centers in Switzerland. Issue 3 (1st April 2018) - Aepli, Patrick; Criblez, Dominique; Baumeler, Stephan; Borovicka, Jan; Frei, Remus
Abstract : Background: Endoscopic full thickness resection (EFTR) by the Full Thickness Resection Device (FTRD) has recently been introduced as a method to allow resection of certain lesions such as adenomatous polyps that would not be resectable by standard polypectomy techniques. We report our clinical experience with FTRD procedures, assessing technical success, completeness of resection (R0 status), rate of histologically proven FTR and safety. Patients and methods: We conducted a retrospective analysis of 33 consecutive patients with colonic polyps treated with FTRD from May 2015 to November 2016. Results: Indications mainly were adenoma recurrence or residual adenoma with nonlifting sign after previous polypectomy. In the 31 cases amenable to EFTR, resection was en bloc and histologically complete (R0) in 87.9% (29/33) of patients. Histologically confirmed complete full thickness resection (FTR) was achieved in 80.6% (25/31). Three post‐procedure bleedings and one perforation were seen. Conclusion: FTRD offers an additional endoscopic approach to treat nonlifting colorectal lesions. EFTR by FTRD appears to be feasible and efficacious in the resection of benign neoplasms of up to 30 mm in diameter and may be an alternative to surgery in selected patients. Given a significant rate of complications, safety is a concern and needs to be assessed in larger prospective studies.